Analysis of Flavonoids, Phenolic Compounds and Essential Oils in Curcuma Aerugenosa Roxb. (Zingiberaceae) - Loo, Wai Sum (2006)
Curcuma aerugenosa Roxb. or locally known as “Temu Hitam” has been used as medicine. It contains useful secondary metabolites. The amount of total phenolic content detected in Curcuma aerugenosa is ranged from 4.5 – 50.9 mg pyrogallol equivalent per g dry weight. Leaf and root extracts exhibited strong antioxidant activity in ferric thiocyanate method (FTC), thiobarbituric acid method (TBA), scavenging effect of the 2,2-diphenyl-1-picyl-hydrazyl (DPPH) radical and conjugated diene formation. In this study, flavonoids and phenolic compounds were determined by using high-performance liquid chromatography (HPLC). The highest content of rutin (1704.7 ± 68.2 μg/g dry weight) and quercetin (1992.4 ± 92.2 μg/g dry weight) were found in leaf unhydrolized and hydrolized extracts respectively. Tuber extract exhibited the highest content of total phenolic compounds (988.6 ± 22.7 μg/g dry weight). The main phenolic compound detected was catechol (615.4 ± 8.2 μg/g dry weight). The essential oils of C. aerugenosa were obtained by hydrodistillation. They were analysed by a gas chromatography mass spectrometry (GC-MS). The major compounds were camphor, 1,8-cineole, β-pinene and camphene. Rhizome oil was found to contain the highest percentage of 1,8-cineole (45.9%) and camphor (15.9%). In this study, Gamborg B5 media with combination of 0.2 mg/L (w/v) 2,4-dichlorophenoxyacetic acid (2,4-D) and 2.0 mg/L (w/v) 6-benzylaminopurine (BAP) was found as the best for initiation of rhizome bud and in vitro grown seedling-leaf callus. A different combination was obtained in callus induction of in vitro grown seedling-petiole and root which was 0.2 mg/L (w/v) of 2,4-D and 1.0 mg/L (w/v) of 6-furfurylaminopurine (kinetin). The callus induced in this study was friable and light yellow in colour. Study on the effect of sucrose concentrations [1, 2, 3 and 4% (w/v)] showed that optimum callus growth was achieved with 3% of sucrose. The highest callus growth of in vitro seedling-leaf and root derived callus were achieved in 0.060 and 0.020 mg/L (w/v) of 2,4-D respectively. Both callus produced 6.382 ± 0.408 and 6.440 ± 0.193 g fresh weight /culture respectively. Dicamba [0.150 mg/L (w/v)] produced the highest production of biomass in rhizome bud (5.603 ± 0.263 g fresh weight /culture) and in vitro grown seedling-petiole (5.458 ± 0.246 g fresh weight / culture) derived callus. Elicitors, yeast extract [20, 40, 60, 80 and 100 mg/L (w/v)] and chitosan [20, 30, 40, 50 and 60 mg/L (w/v)] exhibited different effects on monoterpene (1,8-cineole, linalool, β-pinene and camphor) production. The highest content of 1,8-cineole (0.459 ± 0.020 μg/g fresh weight) and camphor (0.067 ± 0.003 μg/g fresh weight) were produced in 40 and 60 mg/L (w/v) yeast extract added to in vitro grown seedling-petiole derived callus respectively. At 50 mg/L (w/v) of chitosan revealed the highest production of linalool (0.374 ± 0.015 μg/g fresh weight) and β-pinene (0.495 ± 0.021 μg/g fresh weight) in vitro grown seedling-petiole derived callus.